Physiology of Spinal Opioids and its relevance for Pain Management Selection - Borja Mugabure Bujedo (Open Journal of Pain Medicine - Peertechz Publications, 2017)
To use spinal opioids appropriately, it is necessary to understand the pharmacokinetics and clinical pharmacology of these drugs including which opioids produce selective spinal analgesia and which do not. Briefl y, spinal selectivity is highest for hydrophilic opioids and lowest for lipophilic opioids. These differences result from natural variations in the bioavailability of opioids at opioid receptors in the spinal cord. The bioavailability differs because lipophilic drugs are more rapidly cleared into the plasma from epidural and intrathecal spaces, than hydrophilic drugs; consequently, they produce earlier supraspinal side effects and have a considerably shorter duration of analgesic action concerning morphine which can produce delay supraspinal adverse effects.        Morphine is probably the most spinally selective opioid currently used in the intrathecal and epidural spaces for the management of postoperative pain. Continuous epidural administration of fentanyl offers little or no benefi t over the intravenous route. Finally, epidurally administered sufentanil and alfentanil   appear to produce analgesia by systemic uptake and redistribution to brainstem opioid receptors.